2011
DOI: 10.1111/j.1600-0447.2011.01766.x
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal MRI study of cortical thickness, perfusion, and metabolite levels in major depressive disorder

Abstract: Using novel MRI techniques, we have found abnormalities in cerebral regions related to cortical-limbic pathways in MDD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
128
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(145 citation statements)
references
References 90 publications
12
128
4
Order By: Relevance
“…The findings of altered metabolite levels in the PCC in this study support the notion that the PCC may be involved in pathological rumination and self-focused attention in depression; however, metabolite levels in the PCC of depressed patients have not yet been assessed; thus the increase in the resonance peak of mI in the PCC cannot be directly compared with other studies. Nevertheless, the present results of increased mI levels in the PCC in MDDG are in line with studies showing morphological alterations [21,23], lower electroencephalographic activation at rest [24], and higher metabolic activation during rumination [20] in MDD patients. The literature contains reports of functional hyper-connectivity in the PCC and the subgenual-cingulate cortex, correlated with behavioral measures of rumination and brooding in relation to the severity of depression [24]; and of the PCC with the dorsomedial prefrontal cortex, correlated with depressive symptoms in MDD [14].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The findings of altered metabolite levels in the PCC in this study support the notion that the PCC may be involved in pathological rumination and self-focused attention in depression; however, metabolite levels in the PCC of depressed patients have not yet been assessed; thus the increase in the resonance peak of mI in the PCC cannot be directly compared with other studies. Nevertheless, the present results of increased mI levels in the PCC in MDDG are in line with studies showing morphological alterations [21,23], lower electroencephalographic activation at rest [24], and higher metabolic activation during rumination [20] in MDD patients. The literature contains reports of functional hyper-connectivity in the PCC and the subgenual-cingulate cortex, correlated with behavioral measures of rumination and brooding in relation to the severity of depression [24]; and of the PCC with the dorsomedial prefrontal cortex, correlated with depressive symptoms in MDD [14].…”
Section: Discussionsupporting
confidence: 92%
“…Our MDD patients did not differ from healthy controls in the other metabolites measured. The lack of any such significant differences agrees with studies of anterior brain regions and with similar conditions as our patients in the MDDG that found no differences in other brain metabolites like Glu, Cr [31][32][33][34]37], NAA [31,33,34] or Cho [21,31,33]; however, the possibility that these variations are due to the small number of participants cannot be discarded. In conclusion, to the best of our knowledge this is the first evidence of metabolite alterations in the PCC in moderate-to-severe depression in first-episode, medication-naïve patients.…”
Section: Limitationssupporting
confidence: 92%
See 2 more Smart Citations
“…Specifically, remitters showed increased while non-remitters showed decreased cortical thickness in several regions, indicating that structural recovery might occur only if patients respond to treatment. Interestingly, among the entire sample who received pharmacotherapy, only remitters showed increased hippocampal volume and cortical thickness in the rostral middle frontal gyrus, orbitofrontal cortex, and inferior temporal gyrus, whereas a previous study documented increased orbitofrontal cortical thickness in both remitters and non-remitters after antidepressant treatment [33]. Thus, it has been suggested that the reversible alterations in some frontal regions might be associated with remission itself or with antidepressant effects.…”
Section: Mr Imaging Of Brain Morphology and Structurementioning
confidence: 91%